Research in progress: Medical Research Council United Kingdom Refractory Asthma Stratification Programme (RASP-UK). Issue 2 (23rd July 2015) - Heaney, Liam G; Djukanovic, Ratko; Woodcock, Ashley; Walker, Samantha; Matthews, John G; Pavord, Ian D; Bradding, Peter; Niven, Robert; Brightling, Chris E; Chaudhuri, Rekha; Arron, Joseph R; Choy, David F; et al.
Abstract : The UK Refractory Asthma Stratification Programme (RASP-UK) will explore novel biomarker stratification strategies in severe asthma to improve clinical management and accelerate development of new therapies. Prior asthma mechanistic studies have not stratified on inflammatory phenotype and the understanding of pathophysiological mechanisms in asthma without Type 2 cytokine inflammation is limited. RASP-UK will objectively assess adherence to corticosteroids (CS) and examine a novel composite biomarker strategy to optimise CS dose; this will also address what proportion of patients with severe asthma have persistent symptoms without eosinophilic airways inflammation after progressive CS withdrawal. There will be interactive partnership with the pharmaceutical industry to facilitate access to stratified populations for novel therapeutic studies.